2023
DOI: 10.3390/jpm13030495
|View full text |Cite
|
Sign up to set email alerts
|

The U-Shape Relationship between Triglyceride-Glucose Index and the Risk of Diabetic Retinopathy among the US Population

Abstract: Objective: To explore the association of diabetic retinopathy (DR) with TyG index and TyG-related parameters among the United States population. Methods: This cross-sectional study is conducted in adults with diabetes mellitus based on the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Multivariate logistic regression, restricted cubic spline, trend test, receiver operating characteristic curve and subgroup analysis are adopted to uncover the association of DR with TyG index and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Pooled results of seven studies 23 24 26 27 28 30 33 showed that a higher TyG index was associated with a higher risk of DR (OR for the fourth versus the first quartile of TyG index: 1.91, 95% CI: 1.44 to 2.53, p<0.001; I 2 =72%; Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pooled results of seven studies 23 24 26 27 28 30 33 showed that a higher TyG index was associated with a higher risk of DR (OR for the fourth versus the first quartile of TyG index: 1.91, 95% CI: 1.44 to 2.53, p<0.001; I 2 =72%; Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…1. Consequently, eleven records were deemed suitable for the subsequent meta-analysis [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations